PENGARUH KEDISIPLINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT INDOLAND BATAM - Fernando, Kelvin; Wasiman, Wasiman (SCIENTIA JOURNAL, 2021)
Human resource is the most valuable thing for organization in order to achieve goals, different kind of characteristic in society including in organization have an impact in achieving goal that has been set by management. This study aims to analyze the influence of the discipline and work motivation on employee performance at PT Indoland Batam. The lack of discipline and lack of motivation were the main problems in the study, data was collected through questionnaires and distributed to 103 employees who worked at PT Indoland Batam. This study used multiple linear regression statistic which include validity,reability, and R-square Test. Result from the Study showed the coefficient of determination (R2) has a value of 0.659 which means the variable of employee performance can be explained by the variable discipline, and work motivation, of 65,9% while the remaining 34,1% is influeced by other vairable that do not exist in this study.